Modification of the decomposition method of constructing multivariate polynomial regression which is linear with respect to unknown coefficients - Pavlov, Alexander Anatolievich; Holovchenko, Maxim Nikolaevich; Drozd, Valeriia Valeriivna (Національний технічний університет "Харківський політехнічний інститут", 2024)
The authors created a universal method of constructing multivariate polynomial regression given by a redundant representation. The method is synthetic, it organically combines a decomposition method and the modified group method of data handling. First, the decomposition method is implemented, it consists in the decomposition of the multivariate problem into a sequence of subproblems of constructing univariate polynomial regressions and the corresponding systems of linear equations, the variables of which are estimates for the nonlinear terms of the multivariate polynomial regression. Partial cases that guarantee the finding of estimates with a predetermined value of their variances were considered. The formal algorithm for constructing coefficient estimates for nonlinear terms of the multivariate polynomial regression stops working on the first coefficient whose estimation with a predetermined accuracy is not achieved under the specified limitations on the number of tests. The estimation of all coefficients that were not found by the decomposition method is done by a heuristic method, which is an efficient modification of the group method of data handling.

Авторами був створений універсальний метод побудови багатовимірної поліноміальної регресії, заданої надлишковим описом. Метод є синтетичним, що органічно поєднує декомпозиційний метод та модифікований метод групового урахування аргументів. Спочатку реалізується декомпозиційний метод, що полягає в декомпозиції багатовимірної задачі на послідовність підзадач побудови одновимірних поліноміальних регресій та відповідних систем лінійних рівнянь, змінними яких є оцінки при нелінійних членах багатовимірної поліноміальної регресії. Розглянуті часткові випадки, що гарантують знаходження оцінок з наперед заданою величиною їх дисперсій. Формальний алгоритм побудови оцінок коефіцієнтів при нелінійних членах багатовимірної поліноміальної регресії припиняє роботу на першому коефіцієнті, оцінка якого з наперед заданою точністю не досягається при заданих обмеженнях на кількість випробувань. Оцінка всіх коефіцієнтів, що не були знайдені декомпозиційним методом, знаходиться евристичним методом, що є ефективною модифікацією метода групового урахування аргументів.
Модифікація декомпозиційного методу побудови багатовимірної поліноміальної регресії, лінійної відносно невідомих коефіцієнтів
Keywords: regression analysis; multivariate polynomial regression; redundant representation; decomposition method; individual algorithms; least squares method; регресійний аналіз; багатовимірна поліноміальна регресія; декомпозиційний метод; індивідуальні алгоритми; метод найменших квадратів; надлишковий опис